PERTANGGUNGJAWABAN PIDANA TERHADAP PEMILIK DOAMAIN CARA MELAKUKAN CARDING BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 PERUBAHAN ATAS UNDANG-UNDANG MOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Takwa, Megat Kalti; Deliana, Evi; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
One type of cybercrime is carding is a credit card crime, is one form of theft and cheating in the internet world conducted by the perpetrators, to overcome carding law enforcement, the Government of Indonesia to make the Regulation that contains the protection of information and electronic transactions, in the form of Law Number 19 Year 2016 regarding the amendment to Law Number 11 Year 2008 on Information and Electronic Transactions, but what happens today most people know how to do carding from sites or domains available on the internet. Although government blocking has been done, there are still domains that can be accessed by the public. Based on the description above, if the domain of how to do carding only done blocking it, like it is not effective, because it is not able to prevent the development of carding among the public, especially internet users, should the domain owners should be held accountable.When viewed from its type, this research is classified as normative law research. Research proposed to the Act approach and case approach. The Law Approach is conducted by reviewing all laws and regulations relating to legal issues being addressed. Based on the nature of this research is descriptive, which is intended to provide a clear and detailed description of criminal liability review of domain owners how to do carding according to Law Number 19 Year on the amendment to Law No. 11 of 2008 on Information and Electronic Transactions.From result of research which writer do hence can be concluded. First, criminal liability can be given to domain owners how to do carding. Secondly, the weakness of Law Number 19 Year 2016 regarding the amendment to Law Number 11 Year 2008 regarding Information and Electronic Transaction is the absence of defisni about carding therein and there is no carding rules in it.Keywords: Criminal Accountability - Carding - Domain Owner